2018
DOI: 10.3390/dj6040068
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Oral Health Intervention for People Experiencing Homelessness in Scotland: A Participant Observation Study

Abstract: Smile4life is an intervention aimed at improving the oral health of people experiencing homelessness in Scotland. The purpose of this research was to determine how this intervention was being translated from guidance into action. Data concerning Smile4life working practices were collected in three NHS Boards using participant observation. Fieldnotes taken during these observations were analysed using content analysis. This analysis revealed that there were working alliances between the oral health practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…. was closely associated with the individual oral health practitioner, and their personality, experience, communication skills and how they perceived their job role and responsibilities' [28]. Therefore, it was interesting to note that the role of the ability to deliver the Smile4life programme was not only predictive of Implementation Behaviours but was composed of work-related beliefs associated with appropriate knowledge, skills and training together with increased confidence to deliver the programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. was closely associated with the individual oral health practitioner, and their personality, experience, communication skills and how they perceived their job role and responsibilities' [28]. Therefore, it was interesting to note that the role of the ability to deliver the Smile4life programme was not only predictive of Implementation Behaviours but was composed of work-related beliefs associated with appropriate knowledge, skills and training together with increased confidence to deliver the programme.…”
Section: Discussionmentioning
confidence: 99%
“…It revealed that for the delivery of the Smile4life programme a wide range of practitioners from NHS Boards, Local Authority, and Third and other (e.g. Education) sectors was essential [14,28]. A recent four-year research study pointed to the importance of multi-disciplinary working with homeless people across primary and mental health services to promote preventive dental care [29].…”
Section: Discussionmentioning
confidence: 99%
“…Costo del tratamiento 16-52 37 Relación odontólogo paciente y paciente odontólogo 37,41,44 Se evidenció que los pacientes presentaban quejas por el trato que recibían del personal odontológico.…”
Section: Factor De Riesgo Asociado N° De Publicacionesunclassified
“…Returning to the framework of inclusion oral health [5], the papers by Beaton et al [11] and Rodriguez et al [12] on homelessness and Lambert [13] and Yuan [14] on undocumented migrants reflect the very essence of inclusion oral health. The requirement for mixed-methods research to include the voice of experts by experience in the research process is no clearer illustrated than in the papers of Beaton et al [11] and Rodriguez et al [12]. For Beaton et al [11] it is the importance of working alliances between service users, health-care professionals, and the Third Sector that are necessary for the successful implementation of community-based programs to promote oral health.…”
Section: A Synopsis Of the Special-edition Papersmentioning
confidence: 99%
“…The requirement for mixed-methods research to include the voice of experts by experience in the research process is no clearer illustrated than in the papers of Beaton et al [11] and Rodriguez et al [12]. For Beaton et al [11] it is the importance of working alliances between service users, health-care professionals, and the Third Sector that are necessary for the successful implementation of community-based programs to promote oral health. For Rodriguez et al [12] it is the co-design and co-production of oral health and health promotion workshops, using Freire's [15] critical consciousness, that strengthens social interactions and knowledge transfer.…”
Section: A Synopsis Of the Special-edition Papersmentioning
confidence: 99%